Bird diversity at the Adıyaman-Gölbaşı Lakes Important Bird Area (IBA), in southeast Turkey - Büyük, Gökhan; Karakaş, Recep (Wildfowl, 2022)
The diversity of avian species at three lakes (İnekli, Azaplı and Gölbaşı) in the Adıyaman-Gölbaşı Lakes Important Bird and Biodiversity Area (IBA), a unique karst landscape in southeast Turkey, was studied for the first time during 2018–2019. A total of 73 different bird species were detected, from 34 families in 18 orders, of which c. 30% were waterbirds. Fifty species potentially breed at the IBA, whilst 23 occur only in winter or during migration. One – the European Turtle Dove Streptopelia turtur – is of global conservation concern, classed as Vulnerable by the International Union for Conservation of Nature (IUCN) in its Red List of threatened species, and 14 are threatened at the national level. The results suggest that these natural lakes are of great importance for birds. Although the Adıyaman-Gölbaşı Lakes IBA was declared a Nature Park in 2008, illegal hunting, harvesting and reed burning are still major problems in the area. An innovative management approach is required to the protect the habitat, water quality, avian diversity and water flow dynamics in the catchment, in order to protect these natural wetlands and ensure that human activity does not impinge on the integrity of the site.